Mass Spectrometry for Characterizing Plant Cell Wall Polysaccharides - Bauer, Stefan (Frontiers in Plant Science, 2012)
Mass spectrometry is a selective and powerful technique to obtain identification and structural information on compounds present in complex mixtures. Since it requires only small sample amount it is an excellent tool for researchers interested in detecting changes in composition of complex carbohydrates of plants. This mini-review gives an overview of common mass spectrometry techniques applied to the analysis of plant cell wall carbohydrates. It presents examples in which mass spectrometry has been used to elucidate the structure of oligosaccharides derived from hemicelluloses and pectins and illustrates how information on sequence, linkages, branching and modifications are obtained from characteristic fragmentation patterns.